Evaluasi Program Penguatan Pendidikan Karakter (PPK) Di Sekolah - Gus Nafi Unnur Hasan; Isham Adrisna Kurniawan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
One of the policy strategies in the field of education is the Strengthening Character Education Program (PPK), which aims to develop students who possess strong character, noble morals, and personalities aligned with the values of Pancasila. This study aims to highlight how the PPK program is implemented in schools and to examine the evaluation models used. This research employs a qualitative approach with a library research design, using documentation study as the data collection method and content analysis techniques, along with a conceptual approach to obtain a comprehensive understanding. The findings indicate that integrating PPK into intracurricular, co-curricular, and extracurricular activities has been relatively effective. Students have begun to demonstrate character values such as religiosity, discipline, responsibility, and cooperation in their behavior. However, several challenges remain as obstacles in its implementation. In addition, the evaluation reveals that monitoring and evaluation processes have not yet been conducted systematically and consistently. Therefore, this study proposes five models that can be utilized for evaluating PPK programs in schools, namely: (1) CIPP Model; (2) Kirkpatrick Model; (3) Countenance Model; (4) Goal-Oriented Model; and (5) Discrepancy Model (Provus). With the existing supporting factors, the PPK program contributes to steering education toward a more integrative direction. This is because the PPK program promotes a shift in educational paradigms from a sole focus on academic achievement toward a more holistic approach; it supports curriculum and instructional development; fosters a conducive school culture and environment; and strengthens collaboration among schools, families, and communities